Efeitos da suplementação de L-carnitina sobre o lipidograma e a hemoglobina de pacientes submetidos à sessões de hemodiálise - Soares, Glaydson de Oliveira (2019)
Introduction: The hemodialysis procedure consists of removing the toxic substances, water and minerals from the body through the passage of blood through a filter. During dialysis sessions, loss of carnitine may occur in blood plasma concentrations. Carnitine is considered an important cofactor in intermediate metabolism, since it plays an important role in the biosynthesis and functioning of several other important components of our metabolism. As a result, its decrease in plasma levels in the body may result in changes in energy production, excess of toxic products of fat metabolism, changes in lipid profile and oxidation of fatty acids. Carnitine seems to play an important role in metabolism, especially for patients on dialysis. Objective: To verify the effects of L-carnitine supplementation on lipidogram and hemoglobin in patients submitted to hemodialysis sessions. Materials and methods: Experimental Study, with a random sample of chronic kidney disease patients undergoing hemodialysis in a private clinic in the Federal District. The test was performed in two groups, one experimental and the other placebo. The experimental group ingested L-carnitine, one 0.5 gram (500 mg) capsule, given five times a week, after the hemodialysis procedure, over a period of 12 weeks. Data such as anthropometric measures, biochemical evaluation, 24-hour recall and Physical Activity level were collected both before and after 12 weeks with L-carnitine supplementation. Conclusion: It was concluded that supplementation with L-carnitine did not cause positive changes in hemoglobin, total cholesterol, triglycerides, HDL-c and LDL-c, between the pre and post-intervention periods.